Consumption of Non-Prescribed Drugs in Portugal During the Pandemic in 2021 - Aida Isabel Tavares; Aida Isabel Tavares; Pedro Lopes Ferreira; Pedro Lopes Ferreira; Vitor Raposo; Vitor Raposo; Vitor Raposo; Carlota Quintal; Carlota Quintal; Carlota Quintal (International Journal of Public Health, 2023)
Objectives: Portugal liberalised the over-the-counter drugs market in 2005 and provides universal healthcare coverage in a mainly Beveridge-type health system. However, the COVID-19 pandemic has forced healthcare to change how services were delivered, especially increasing remote consultations in primary care. This analysis aims to find the drivers for taking non-prescribed drugs during the pandemic in Portugal. Specifically, it seeks to understand the role of taking prescribed drugs and attending remote medical appointments in the self-medication decision.Methods: In this observational study, we used data collected during the pandemic in Centre Region of Portugal and estimated logistic regression for the whole sample and stratified by sex.Results: The main findings show that people taking prescribed medications and attending a remote consultation are more likely to take non-prescribed drugs. Also, reporting unmet healthcare needs seems to motivate people to choose self-medication.Conclusion: Policy implications are pointed out concerning the health risks raised from self-medication, the role of the pharmacist advising non-prescribed drugs, and the related health risks arising from unmet healthcare needs.